Manajemen Pembinaan Prestasi Cabang Olahraga Bolavoli Sidoarjo Jaya - Ardhiansyah Rahmat Firdaus; Lutfhi Abdil Khuddus (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Volleyball is a large ball game played by two opposing teams. The game is played by 2 teams of 6 players each fighting to be the first to reach 25 points. There are 4 important roles in a team, namely Pitcher (or Setter), Spiker (Smash), Libero and Defender (Defender). Tosser or pengmpang is a person whose job is to pass the ball to his teammate and dictate the flow of the game. The spiker's job is to hit the ball so that it lands in the opponent's defense zone. A libero is a defender who is free to enter and exit but may not hit the ball over the net. Defender is a player who defends to fend off enemy attacks. Pembinaan Sidoarjo Jaya is a volleyball coach management organization. Facing these developments, the Sidoarjo region, especially the Disporapar Kab. Sidoarjo hopes that this training will result in better performance and be able to lift the volleyball court from a lower level to a higher level. The aim of the researcher is to find out comprehensively how the management of volleyball coaches in Sidoarjo Jaya is related to the development of achievement, inhibiting factors and management of Sidoarjo Jaya's development results. This type of research is a descriptive research method with observation methods, data collection methods through interviews, questionnaires and topic documentation. Sidoarjo Jaya managers, coaches and athletes participated in this study, totaling 45 people consisting of 2 managers, 4 coaches and 39 athletes. The data analysis technique used is a data analysis technique using the percentage description method. As a result, the athlete's perception of human resources was in the high category with an average of 92.62, while the athlete's perception of facilities was in the high category with an average of 95.77, reflecting the athlete's perception of the training program. It is in the low category for which the average value was obtained. 96.95, high and low category training program trainers' average of 90.50, high category human resource trainers' average of 49.75, managers' perception of human. , the average of 46.00 high range and low category resources representing the manager's perception of the facility by determining an average of 94.50.